Accumulating too much stuff: what is hoarding and what is not?. (August 2015) - Snowdon, John
Objective: This paper considers the meaning of the terms hoarding, collecting and accumulation, with a focus on what is abnormal and what is not. Conclusions: Hoarding is an adaptive behaviour. When hoarding is excessive and interferes with people's lives, it is a disorder. A central feature of hoarding disorder is accumulation of items due to unwillingness to discard them. This must be distinguished from abnormal accumulation of material caused by poor motivation or unawareness concerning the need to discard.